Africa: Resource Challenges to Doctoral Education - Tamrat, Wondwosen; Fetene, Getnet Tizazu (International Higher Education, 2021)
This article examines the provision of doctoral education in Ethiopia and its implications for African higher education. Despite the role given to doctoral education toward achieving economic development and improving the quality of higher education, the resources for running PhD programs are lacking in many African countries. More efforts should be directed to building institutional capacity and availing the resources needed to run successful doctoral programs.